Business strategy for halal food-based businesses regional (Minangkabau) in Padangsidimpuan City - Nasution, Jafar; Hayati, Rahma; Hardana, Ali (Institute of Computer Science (IOCS), 2024)
Mix marketing is the main marketing design consisting of product, price, place, and promotion. The sale of regionally-based halal food is still lacking promotion both through print media and through social media. Although Minang restaurants have many enthusiasts, in reality they have not utilized online ordering. This study aims to analyze how the concept of marketing strategy includes product, price, location, place, target, sales position and market segment for Minang culinary businesses in Padangsidimpuan City. This research uses qualitative anthropological methods with expioratory and inductive methods. Segmentation strategy, this segment is more directed to all communities. Regarding the positioning strategy, this strategy focuses on improving service quality. Regarding the product strategy, they business actors have produced halal food and drinks, as for the price strategy, the price offered by the producer is a competitive price related to promotion, they promote their goods by word of mouth